The nucleolar protein SAHY1 is involved in pre-rRNA processing and normal plant growth. Issue 3 (29th December 2020) - Hsu, Pei-jung; Tan, Mei-Chen; Shen, Hwei-Ling; Chen, Ya-Huei; Wang, Ya-Ying; Hwang, San-Gwang; Chiang, Ming-Hau; Le, Quang-Vuong; Kuo, Wen-Shuo; Chou, Ying-Chan; Lin, Shih-Yun; Jauh, Guang-Yuh; et al.
Abstract: Although the nucleolus is involved in ribosome biogenesis, the functions of numerous nucleolus-localized proteins remain unclear. In this study, we genetically isolated Arabidopsis thaliana salt hypersensitive mutant 1 ( sahy1 ), which exhibits slow growth, short roots, pointed leaves, and sterility. SAHY1 encodes an uncharacterized protein that is predominantly expressed in root tips, early developing seeds, and mature pollen grains and is mainly restricted to the nucleolus. Dysfunction of SAHY1 primarily causes the accumulation of 32S, 18S-A3, and 27SB pre-rRNA intermediates. Coimmunoprecipitation experiments further revealed the interaction of SAHY1 with ribosome proteins and ribosome biogenesis factors. Moreover, sahy1 mutants are less sensitive to protein translation inhibitors and show altered expression of structural constituents of ribosomal genes and ribosome subunit profiles, reflecting the involvement of SAHY1 in ribosome composition and ribosome biogenesis. Analyses of ploidy, S-phase cell cycle progression, and auxin transport and signaling indicated the impairment of mitotic activity, translation of auxin transport carrier proteins, and expression of the auxin-responsive marker DR5::GFP in the root tips or embryos of sahy1 plants. Collectively, these data demonstrate that SAHY1, a nucleolar protein involved in ribosome biogenesis, plays critical roles in normal plant growth in association with auxin transport and signaling. Abstract : SALT-HYPERSENSITIVE MUTANT 1, a nucleolar protein involved in ribosome biogenesis, regulates the auxin-mediated development of vegetative and reproductive tissues.